Research progress on extraction, purification, structure and biological activity of Dendrobium officinale polysaccharides - He, Yuan; Li, Lin; Chang, Hao; Cai, Bin; Gao, Huajun; Chen, Guoyu; Hou, Wen; Jappar, Zubaydan; Yan, Yizhe (Frontiers in Nutrition, 2022)
Dendrobium officinale Kimura et Migo (D. officinale) is a traditional medicinal and food homologous plant that has been used for thousands of years in folk medicine and nutritious food. Recent studies have shown that polysaccharide is one of the main biologically active components in D. officinale. D. officinale polysaccharides possess several biological activities, such as anti-oxidant, heptatoprotective, immunomodulatory, gastrointestinal protection, hypoglycemic, and anti-tumor activities. In the past decade, polysaccharides have been isolated from D. officinale by physical and enzymatic methods. and have been subjected to structural characterization and activity studies. Progress in extraction, purification, structural characterization, bioactivity, structure-activity relationship and possible bioactivity mechanism of polysaccharides D. officinale were reviewed. In order to provide reference for the in-depth study of D. officinale polysaccharides and the application in functional food and biomedical research.